ChemInform Abstract: Stabilization of Tetravalent 4f (Ce), 5d (Hf), or 5f (Th, U) Clusters by the [α‐SiW9O34]10‐ Polyoxometalate. Issue 45 (November 2015) - Duval, Sylvain; Beghin, Sebastien; Falaise, Clement; Trivelli, Xavier; Rabu, Pierre; Loiseau, Thierry
Abstract The crystal structures of compounds (IV), (VII), (X), and (XIII) are determined by single crystal XRD.